2018
DOI: 10.1080/09168451.2018.1459466
|View full text |Cite
|
Sign up to set email alerts
|

Zebularine exerts its antiproliferative activity through S phase delay and cell death in human malignant mesothelioma cells

Abstract: Malignant mesothelioma is an asbestos-related aggressive tumor and current therapy remains ineffective. Zebularine as a DNA methyltransferase (DNMT) inhibitor has an anti-tumor effect in several human cancer cells. The aim of the present study was to investigate whether zebularine could induce antiproliferative effect in human malignant mesothelioma cells. Zebularine induced cell growth inhibition in a dose-dependent manner. In addition, zebularine dose-dependently decreased expression of DNMT1 in all malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, with the addition of ZEB administration, the demethylation effect could be maintained [84]. Therefore, it also combines with azacytidine and decitabine and displays much safer in various cancer treatments, such as AML and EBV-positive Burkitt's lymphoma [95].…”
Section: Dnmt Inhibitors (Dnmtis)mentioning
confidence: 99%
“…However, with the addition of ZEB administration, the demethylation effect could be maintained [84]. Therefore, it also combines with azacytidine and decitabine and displays much safer in various cancer treatments, such as AML and EBV-positive Burkitt's lymphoma [95].…”
Section: Dnmt Inhibitors (Dnmtis)mentioning
confidence: 99%
“…It displays high stability as it inhibits both DNMTs and cytidine deaminase, and it is stable in acidic and neutral pH, enabling oral administration [ 71 ]. Moreover, zebularine has low cytotoxicity, which might translate into longer treatments with low doses to maintain a demethylated state [ 71 ], as well as an apparent specificity for cancer cells and not fibroblasts [ 72 , 73 ]. Zebularine leads to S-phase delay and cell death in mesothelioma cells [ 72 ], causes formation of replication-dependent double-strand DNA breaks [ 74 ], and enhances colon cancer cell immunogenicity [ 75 ].…”
Section: Dnmt Inhibitorsmentioning
confidence: 99%
“…Moreover, zebularine has low cytotoxicity, which might translate into longer treatments with low doses to maintain a demethylated state [ 71 ], as well as an apparent specificity for cancer cells and not fibroblasts [ 72 , 73 ]. Zebularine leads to S-phase delay and cell death in mesothelioma cells [ 72 ], causes formation of replication-dependent double-strand DNA breaks [ 74 ], and enhances colon cancer cell immunogenicity [ 75 ]. Nevertheless, high concentrations of zebularine are needed to achieve demethylation levels similar to those of DAC since it forms a reversible complex with DNMTs, with slow dissociation kinetics [ 76 ], hindering the transition to clinical practice [ 57 , 71 ].…”
Section: Dnmt Inhibitorsmentioning
confidence: 99%
“…Zebularine was developed to counter the shortcomings of DNMTI 5-azacytidine. Zebularine was reported to be safer than 5-azacytidine for the treatment of cancers in Epstein–Barr Virus (EBV) carriers and proposed to be used against tumors possessing EBV (Takemura et al, 2018).…”
Section: Regulation Of Colorectal Cancer By Epigenetic Mechanismmentioning
confidence: 99%
“…These studies indicated that zebularine could effectively target both DNMT inhibitors and non-DNMT inhibitors. In lymphoma cells, zebularine reactivates silenced E-cadherin, which suggests its capacity to reverse the EMT (Takemura et al, 2018).…”
Section: Regulation Of Colorectal Cancer By Epigenetic Mechanismmentioning
confidence: 99%